Gender, work and population in sub-Saharan Africa - Adepoju, A.; Oppong, C. (1994)
This volume looks at various aspects of the culturally prescribed roles of women and men - that is, gender issues - in sub-Saharan Africa and their relevance to the recording of facts upon which national policies and plans promoting the welfare of labour and national economic development are supposed to be based. Contributions: Introduction (Christine Oppong) - The demographic profile: sustained high mortality & fertility & migration for employment (Aderanti Adepoju) - Wives & mothers: female farmers in Africa (Ann Whitehead) - Agricultural policies & women producers (Constantina Safilios-Rothschild) - Measuring women's participation in the African labour force (Richard Anker) - Assessing women's economic contributions in domestic & related activities (Luisella Goldschmidt-Clermont) - Gender-sensitive statistics & the planning process (E. Oti Boateng) - Women's work, child-bearing & child-rearing over the life cycle in Ghana (Ann K. Blanc & C.B. Lloyd) - Women's work & fertility in Zimbabwe: ending underdevelopment with change (Robert E. Mazur & Marvellous Mhloyi) - Women, work & fertility in Swaziland (Aderanti Adepoju) - Breast-feeding & birth spacing: erosion of West African traditions (Yaw Ofosu) - Family planning & welfare in northern Ghana (Katharine Abu) - The grandmother & household viability in Botswana (Benedicte Ingstad).